Acute blindness as a presenting sign of left atrial myxoma in a pediatric patient: A case report and literature review. Issue 38 (September 2019) - Yi, Seo Yeon; Han, Min Jeong; Kong, Young Hwa; Joo, Chan Uhng; Kim, Sun Jun
Abstract: Rationale: Central retinal artery occlusion (CRAO) due to cardiac myxoma primarily occurs in elderly individuals. Early detection and surgical resection of myxoma are extremely important because CRAO causes complete blindness in most cases. However, due to the extremely low incidence of CRAO caused by cardiac myxoma in the pediatric age group, such condition is rarely reported. Patient concerns: A 16-year-old female patient visited our hospital due to sudden onset of vision loss in the left eye, dysarthria, and right-sided hemiplegia. Diagnoses: She was diagnosed with CRAO via fundoscopy. Results showed a cherry-red spot, indicating CRAO. Brain magnetic resonance imaging (MRI) revealed multifocal diffusion-restricted foci, particularly in the left frontal lobe. Echocardiography revealed a left atrial mass measuring 4.21 cm × 2.25 cm. The mass was attached to the interseptum and moved along the inflow of the mitral valve. Cardiac computed tomography (CT) revealed an enhanced mass measuring 3 cm × 2.2 cm × 3 cm and with irregular margin on the anterior wall of the left atrium and the border of the fossa ovalis. Interventions: The patient underwent surgical excision under general anesthesia. Intraoperative finding showed a huge, jelly-like, and extremely friable mass. Pathological examination confirmed myxoma. Outcomes: During a follow-up of 2 years after diagnosis, she did not present with other neurological deficits and no residual mass was observed on echocardiography. However, visual impairment of the left eye persisted. Lessons: Most patients with CRAO may present with other mild symptoms that are often be neglected before CRAO development. We recommend that patients who present with frequent syncopal attack or symptoms of transient ischemic attack should undergo echocardiography.